Kepemilikan Manajerial, Kepemilikan Institusional, dan Kepemilikan Asing terhadap Manajemen Laba - Martinus Robert Hutauruk; Novi Yanti; Rizki Nurjannah (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
Earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique was purposive sampling and the sample in this study was 10 samples for 5 years. Panel data regression analysis was used to analyze the data. The results of this study prove that institutional ownership and foreign ownership affect earnings management. The implication of institutional ownership is that some investors cooperate with company managers to obtain the desired profit, rather than monitoring to minimize earnings management actions, while foreign ownership which has an effect on the higher the level of foreign ownership shares in a company can reduce earnings management actions. With results indicating an increase in foreign ownership shares can affect earnings management actions.